2011
DOI: 10.1103/physrevc.84.054910
|View full text |Cite
|
Sign up to set email alerts
|

Quark polarization in a viscous quark-gluon plasma

Abstract: Quarks produced in the early stage of non-central heavy-ion collisions could develop a global spin polarization along the opposite direction of the reaction plane due to the spin-orbital coupling via parton interaction in a medium that has finite longitudinal flow shear along the direction of the impact parameter. We study how such polarization evolves via multiple scattering in a viscous quark-gluon plasma with an initial laminar flow. The final polarization is found to be sensitive to the viscosity and the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 62 publications
(84 reference statements)
2
78
0
1
Order By: Relevance
“…(1) The noncentral heavy-ion collisions can generate fluid vorticity in the interaction region [252][253][254][255][256][257][258]. The fluid vorticity can also induce anomalous transports, generally called the chiral vortical effect (CVE) [20][21][22] (earlier suggestion is given in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The noncentral heavy-ion collisions can generate fluid vorticity in the interaction region [252][253][254][255][256][257][258]. The fluid vorticity can also induce anomalous transports, generally called the chiral vortical effect (CVE) [20][21][22] (earlier suggestion is given in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In non-central high-energy heavy-ion collisions, the large orbital angular momentum present in the colliding system can lead to non-vanishing local vorticity in the hot and dense fluid [1][2][3][4][5][6]. The vorticity induced by global orbital angular momentum in the fluid can be considered as local rotational motion of particles [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The drastic thermal motion of particles will decrease the quark polarization rate, which according to Ref. [11] is inversely proportional to the collision energy. On the other hand, simulating results by a multi-phase transport (AMPT) model has shown that the averaged classical vorticity decreases with the collision energy [36,37], which, of course, leads to the decline of global polarization.…”
mentioning
confidence: 99%
“…Afterwards, more experimental research was launched continuously, including nucleon collisions and heavy ion collisions [3][4][5][6][7][8][9]. Theoretical studies have also been under way synchronously with the experiments [10][11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation